Informal learning among teenagers through video games: a qualitative analysis of experiences, game modes and didactic benefits - Milan Matijević; Tomislav Topolovčan (University of Maribor Press, 2019)
The paper analyzes the positive effects of video games on teen development and on teenagers' informal learning. The participants in the research were teenagers. The analysis and interpretation of games and explanations of their pedagogical merit indicate that players recognize their value for informal learning. Latent characteristics of video games include positive elemests such as taking responsibility, teamwork, sense of belonging, creativity, multiculturalism, personal virtues and values, emotion management, learning new information and skills, motor skills development and professional orientation. In that respect, it is possible to conclude that gaming may help in the development of certain abilities important for informal as well as formal learning in today's digital age.